Sosialisasi Pencegahan Bullying Di SDN 85 Kota Pekanbaru: Ciptakan Generasi Tanpa Kekerasan - M. Rafi; Dwi Sekar Wangi; Alika Fiorella Alanda; Annisa Syukri Pitopang; Diva Nura Asmara; Afisya Madhani; Alifa Saira Putri; Dio Dwi Prayoga; Fernanda Adrian; Firman Erikson Siahaan; Hiliya Safanah Zahra; Nurvica Bona Bilqis; Sopiyani Sopiyani (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Bullying is an act of aggression, intentional, committed by an individual or group of individuals, to inflict pain, intimidate and terrorize to gain power and recognition. This socialization activity is intended to educate students about the negative impacts of bullying and the proper prevention methods. This activity is also in accordance with Sustainable Development Goal 4, which is quality education that supports a safe and inclusive learning environment for students to understand issues related to bullying and their prevention efforts. The methods used are interactive material delivery, discussion questions, pre-test and post-test questionnaires involving all participants so that the learning process can run interactively. The enthusiasm of students during the implementation of a series of socializations was very high, which was marked by an increase in the understanding of creating a safe, comfortable, and bullying-free school environment.